Korelasi Persepsi Kemampuan Metakognitif dan Kemampuan Berpikir Kritis Siswa SMA Di Masa Pandemi Covid-19 - Chinta Celi Ayu Cendana; H Harjono (Phenomenon : Jurnal Pendidikan MIPA, 2021)
One of the student abilities needed in the 2013 curriculum is metacognitive abilities. Some research results show that metacognitive abilities affect critical thinking skills. Researchers are interested in explaining the relationship between metacognitive abilities and critical thinking skills in learning chemistry on acid-base titration material. The formulation of the problem and the purpose of this study is how to correlate perceptions of metacognitive abilities to critical thinking skills of XI grade high school students at SMA Unggulan Nurul Islami Mijen during the Covid-19 pandemic. The research sample was taken by using purposive sampling technique. The sample used was 30 students from class XI MIPA SMA Unggulan Nurul Islami Mijen. The research data were obtained using a metacognitive perception questionnaire and a critical thinking ability test. The data obtained were analyzed using descriptive analysis techniques and analysis techniques PLS (Partial Least Square) assisted by SmartPLS 3.0 software. The results of the analysis using the PLS technique show that there are three models that have been successfully obtained, namely model 1 which is called the initial model, model 2 estimation from model 1 and model 3 as the final model. Based on the justification of the analysis, model 3 is considered the best research model. In model 3, the correlation value of perceived metacognitive ability to students' critical thinking abilities is 0.360, so it can be concluded that students have a correlation between perceptual metacognitive abilities and critical thinking abilities.